Analysis of Trip Generation Modeling in The Higher Education Area: A Case Study of UNISSULA, Semarang City - Firdaus, Ilham; Putra Muttaqien, Abied Rizky (Jurnal Teknik Sipil dan Perencanaan, 2025)
Semarang City, the capital of Central Java Province, has various activities, one of which is higher education. The location of higher education activities on main roads can increase road service (LOS). This study aims to model the number of trips to UNISSULA and alternative routes in the event of a flood. This study uses quantitative methods with multiple linear regression analysis. One dependent variable and eight independent variables will be modeled using SPSS 26—the number of respondents representing the movement of 398 people. Based on the analysis results, the LOS level of UNISSULA Road on weekdays is 0.22 for attraction and 0.21 for generation. Then, on weekends, the LOS level of UNISSULA Road is 0.16 for attraction and 0.16 for generation. In the Jalan Raya Kaligawe section, the LOS value is 0.50 on weekdays and 0.55 on weekends. The resulting regression model is Y weekday pull = 752.624 + 3.138X1 + 7.418X2, Y weekday generation = 3728.412-4.635X1-8.075X2, Y weekend pull = 270.00 + 3.117X1 + 5.979X2, and Y weekend generation = 2493.733-2.841X1-4.938X2. The resulting model can be used by urban planners and policymakers to optimize traffic management and reduce congestion in the UNISSULA area. The traffic management strategies that can be applied to the resulting model include optimizing public transport use, encouraging shared vehicles, developing pedestrian and bicycle infrastructure, travel time management, and increasing the capacity of alternative roads.